Human Visceral Leishmaniasis: lethality and time from suspicion to treatment in an endemic area in Brazil - Santos, Millena Pereira dos; Ferreira, Jardel Martins; Giannoccaro da Silva, Marco Augusto [UNESP]; Almeida, Katyane de Sousa (Univ Santa Cruz Do Sul, 2022)
Background and objectives: human visceral leishmaniasis (HVL) are a persistent public health problem, configuring a challenge to reduce its lethality. In order to evaluate the factors associated with lethality, this study emphasizes the time elapsed from suspicion to treatment of HVL, in the years 2015 to 2019, in the municipality of Araguaina-TO, an area of intense transmission. Methods: an epidemiological study of case series with longitudinal follow-up with information extracted from HVL notification and investigation forms. The relative risk (RR) was used as a measure of the strength of association for death, being calculated with confidence intervals (95% CI) estimated by the Wald test. Time intervals were represented in days by box plot as medians (Md). Results: of the 191 cases of HVL, 179 (93.72%) were cured and 12 (6.28%) had a fatal outcome. There was no association of risk of death by sex, education, race, being significant only by age in the age groups of young (RR= 16.09) and older adults (RR=7.08). The time from suspicion to treatment in children was shorter (0-35 days, Md=12) than that of older patients (4-44 days, Md=18) and in those who died (7-65 days, Md=20) highlighting greater inopportunity of healing in these last two groups. Conclusion: late diagnosis was a determining indicator for worse outcomes, five days made the difference between the group with an outcome for cure with the group of those who died, highlighting the need to shorten the wait for treatment.
Keywords: Visceral leishmaniasis; Delayed Diagnosis; Mortality